Dynamic economic dispatch solution using particle swarm optimization: article - Muhamad Hassan, Muhammad Azuwam; Nik Ismail, Nik Fasdi (2012)
This paper present particle swarm optimization (PSO) technique to solve the dynamic economic dispatch (DED) problem for the determination of the optimal schedule of output powers from differents units (denerator) at the minimum cost possible over a certain period.